Sweat, tears, and beyond: advanced wearable sensors for personalized health and athletic performance - Gulgosteren, Erkan; Agrali Ermis, Sermin; Algin Toros, Aydolu; Toros, Turhan; Serin, Emre; Sekeroglu, Mustafa Onder; Bahadır Kayisoglu, Numan (Frontiers in Bioengineering and Biotechnology, 2025)
This review investigates the transformative potential of wearable sensors for body fluid monitoring in sports and healthcare. These devices offer a non-invasive, real-time, in-situ glimpse into our health by continuously tracking vital biomarkers found in sweat, saliva, urine, and tears. We discuss various sensor technologies, including electrochemical, optical, and microfluidic, and the innovative materials like hydrogels and nanocomposites that enable their functionality. The integration of RFID and flexible electronics is also examined, highlighting how these advancements improve the connectivity, portability, and user-friendliness of the sensors. Moreover, we delve into the advanced manufacturing techniques, such as 3D printing, that are crucial for crafting these sophisticated devices with high precision and adaptability. In prospect, this article evaluates the transformative potential of integrating these in-situ sensors with artificial intelligence and machine learning, envisioning a paradigm shift in health monitoring and athletic performance optimization.